Valoração de resíduos e subprodutos agroindustriais utilizando reatores anaeróbios em fermentação escura para produção de hidrogênio, etanol e ácidos orgânicos - Lopes, Helberth Júnnior Santos (Universidade Federal de São Carlos, 2015)
The aim of this work was to evaluate hydrogen, ethanol and organic acids productions from several substrate, including, agribusiness byproducts, such as cheese whey, hydrolyzed cellulose and crude glycerol, and simple substrates, such as glucose and xylose. Three continuous reactors were operated. A thermophilic Anaerobic Fluidized Bed Reactor (AFBR), denominated R1, was operated to evaluate hydrogen production from hydrolyzed cellulose. The substrate concentration was 2000mg.L-1 different Hydraulic Retention Times (HRT) ranging from 24 to 6h. Another thermophilic RALF (R2) was used in order to evaluate xylose and glucose co-fermentation to produce hydrogen and ethanol. R2 was operated with HRT starting in 16 h and decreased to 1 h. The substrates concentration was 2000mg.L-1 of each carbohydrate. Hydrogen and propionic acids production was evaluated in Expanded Granular Sludge Bed (ESGB) reactor, operating with Cheese Whey (CW) and Crude Glycerol (CG) co-fermentation in several ratios: 5:1, 5:2, 5:3, 5:4 and 5:5 (m/m) and decreasing HRT from 8 to 0.5h. For R1, maximum yield was 1.1 mol H2.mol-1 glucose, obtained in HRT of 8h. In R2, the consumption of both substrates was verified. However, glucose consumption was higher than xylose. Maximum hydrogen yield, 0,401 mol H2 mol-1 glucose equivalent was achieved in HRT of 16h. Maximum ethanol yield, 0,25mol EtOH.mol- 1glicoseequivalent, occurred in 0.5h HRT. The EGSB reactor maximum hydrogen yield, 0,120 mmol.g-1DQO, was obtained using a 5:1 CW/RG ratio and HRT of 8h. Maximum propionic acid, 0,99g.g-1substrate, was also verified in HRT of 8h, however, with a 5:3 CW/CG ratio. At the end of the work it was made comparison of three reactors. Toward the hydrogen yield the greatest result was obtained by R1 with the value of 2,02 mmolH2.g-1DQO applied, this result occurred in HRT of 8h. In relation to energy efficiency the highest value was observed in R2, 47kJ.h-1.L-1, obtained in HRT of 0,5h.
Keywords: Hidrogênio; Etanol; Xilose; Hidrolisado; Glicerol; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA